Islamic Spiritual Leadership in Early Childhood Education: A Systematic Review of Models for Quality and Character Development - Risnajayanti, Risnajayanti; Akib, Irwan; Mawardi, Amirah (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study aims to examine the concept and application of Islamic spiritual leadership in realizing quality and character-based Early Childhood Education (PAUD). The method used is a Systematic Literature Review (SLR) by analyzing 15 relevant national and international articles, obtained from Google Scholar, ResearchGate, Scopus, DOAJ, and Garuda Dikti databases. The results of the study indicate that Islamic spiritual leadership in PAUD emphasizes exemplary behavior, the moral values of knowing-feeling-acting, and the application of the characteristics of the Prophet Muhammad SAW, namely shidiq, amanah, tabligh, and fathanah. Implementation strategies found include teacher training, habituation of religious values, curriculum integration, extracurricular activities, congregational prayer, and strengthening school culture. Obstacles that arise include limited teacher competence, student diversity, and limited time and resources. This leadership model has a positive impact on improving the quality of education, character formation, discipline, and intrinsic motivation of children. The novelty of this study lies in the synthesis of literature that comprehensively links Islamic spiritual leadership with efforts to improve the quality and character formation of early childhood. This study also recommends the importance of ongoing training for educators and empirical studies to strengthen the effectiveness of the Islamic spiritual leadership model in early childhood education institutions. Thus, the results of this study emphasize that Islamic spiritual leadership is not only conceptually relevant, but also constitutes a strategic foundation in realizing quality and superior character PAUD in the modern era.